The Development of a Web-Based Self-Learning Module for a Split Unit Air-Conditioning System - Abdul Rani, Muhamad Danial; Mohamad, Marlina (Research and Innovation in Technical and Vocational Education and Training, 2023)
Self-learning is a learning process carried out by students where the students have authority in managing the process of knowledge absorption without being bound by place and time. Despite this, the diversity of learning styles among the students as well as the lack of self-learning modules catalyzed the product development of this research. The objective of this study is to design and develop a web-based self-learning module for the topic of Split Unit Air Conditioning Systems. Furthermore, the research product has gone through a functionality evaluation among three technical design experts, two content experts as well as a usability evaluation among 27 students. The development of this learning module is using google sites software to provide results that are easier and suitable for users. This study also uses the ADDIE Model as a product development reference as well as Gagne's Nine Events of Instruction Model as a product content reference. Based on the analysis, the level of functionality of the product is rated as high among the experts involved. Next, for testing the usability of the product, students rated it as high for all aspects which is presentation design, content and user-friendliness. This self-learning module is expected to be used to increase understanding as well as a revision material among students for that topic. Nevertheless, future researchers can continue by studying the effectiveness of student learning using the module. Keywords: Self-learning, web-based learning, ADDIE, Gagne's